Unsteady/Steady Natural Convection Flow of Reactive Viscous Fluid in a Vertical Annulus - B.K. Jha; A.K. Samaila; A.O. Ajibade (International Journal of Applied Mechanics and Engineering, 2013)
This paper presents both analytical and numerical analyses of a fully developed unsteady/steady natural convection flow of a reactive viscous fluid in an open ended vertical annulus. Analytical expressions for velocity, temperature, skin-friction and rate of heat transfer are obtained after simplifying and solving the governing differential equations with reasonable approximations. The interesting result found in this study is that an increase in non-dimensional time (t) , increases both temperature and velocity profiles until a steady-state value is attained. Subsequent results obtained by numerical calculations show excellent agreement with analytical results.